2020
DOI: 10.1136/bmj.m513
|View full text |Cite
|
Sign up to set email alerts
|

Egg consumption and risk of cardiovascular disease: three large prospective US cohort studies, systematic review, and updated meta-analysis

Abstract: Objective To evaluate the association between egg intake and cardiovascular disease risk among women and men in the United States, and to conduct a meta-analysis of prospective cohort studies. Design Prospective cohort study, and a systematic review and meta-analysis of prospective cohort studies. Setting Nurses’ Health Study (NHS, 1980-2012), NHS II (1991-2013), Health Professionals’ Follow-Up Study (HPFS, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
77
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(90 citation statements)
references
References 65 publications
11
77
0
2
Order By: Relevance
“…Two cohort studies were identified by a manual search ( 5 , 15 ). Ultimately, 16 articles involving 24 cohort studies were included ( 4 9 , 12 , 13 , 15 22 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two cohort studies were identified by a manual search ( 5 , 15 ). Ultimately, 16 articles involving 24 cohort studies were included ( 4 9 , 12 , 13 , 15 22 ).…”
Section: Resultsmentioning
confidence: 99%
“…Limited data on egg intake pattern were reported in the original studies. Most studies reported whole-egg intake or eggs consumed as components of recipes (6,8,9,12,13,16,19,21,22), including fried, boiled, poached, deviled, or egg salad, but baked dishes (such as custards and puddings) were not included (6,19). Other studies did not report the egg intake pattern (4,5,7,15,17,18,20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 In contrast, scientific misinformation (e.g., regarding vaccination and stem cell therapies) travels at Internet speed. [9][10][11][12] And still other health-related recommendations, such as whether to take aspirin for primary prevention of cardiovascular disease 13,14 or whether eating eggs 15,16 or red meat is harmful, seem to be cyclical, engendering confusion at best and mistrust of science at worst. 17 As Arthur D. Little stated nearly 100 years ago, "In the past the world suffered grievously from lack of knowledge; today it suffers from its rejection or misapplication."…”
mentioning
confidence: 99%
“…The residue of this hypothesis has been the impetus for a large body of research, including most recently, the substantial contribution by Drouin-Chartier and colleagues in a linked article in The BMJ (doi:10.1136/bmj.m513). 4…”
mentioning
confidence: 99%